Influence of Photoperiod on The Induction of in Vitro Porang (Amorphophallus muelleri Blume) Shoots - Normasari, Rut (Jurnal Biologi Tropis, 2024)
The tuber plant known as porang (Amorphophallus muelleri Blume) has a lot of industrial potential. Due to the restricted supply of seeds, porang production is still minimal despite its many advantages, which make it an export commodity with plenty of prospects. An alternate method for quickly and efficiently producing high-quality porang seeds in big quantities is in vitro culture. One significant element influencing in vitro shoot induction is photoperiod. The study aims to obtain the best photoperiod for in vitro porang shoot induction. This study applied a completely randomized design with 7 photoperiod treatments (0, 4, 8, 12, 16, 20 and 24 hours) and 5 replications. The percentage of explants that develop shoots, the number of shoots per explant, and the total number of shoots are all examples of observation parameters. An additional 5% Duncan test was performed to determine whether there was a significant impact on the observation variables after the observation data was analyzed using analysis of variance. The results showed that a 16-hour photoperiod produced the highest porang shoot induction in all observation variables in the 4th and 8th weeks.